2012
DOI: 10.1038/ncomms1675
|View full text |Cite
|
Sign up to set email alerts
|

EphB3 suppresses non-small-cell lung cancer metastasis via a PP2A/RACK1/Akt signalling complex

Abstract: Eph receptors are implicated in regulating the malignant progression of cancer. Here we find that despite overexpression of EphB3 in human non-small-cell lung cancer, as reported previously, the expression of its cognate ligands, either ephrin-B1 or ephrin-B2, is significantly downregulated, leading to reduced tyrosine phosphorylation of EphB3. Forced activation of EphB3 kinase in EphB3-overexpressing non-small-cell lung cancer cells inhibits cell migratory capability in vitro as well as metastatic seeding in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 46 publications
5
92
0
Order By: Relevance
“…Overexpression of EPHB3 has been reported in NSCLC and is associated with the promotion of a metastatic phenotype in these tumors. The ability of EPHB3 to drive metastasis is believed to be independent of its kinase activity [64,65]. EPHB3 was amplified in 37% of SQCC samples evaluated by the TCGA [8,41].…”
Section: Ephb3mentioning
confidence: 99%
“…Overexpression of EPHB3 has been reported in NSCLC and is associated with the promotion of a metastatic phenotype in these tumors. The ability of EPHB3 to drive metastasis is believed to be independent of its kinase activity [64,65]. EPHB3 was amplified in 37% of SQCC samples evaluated by the TCGA [8,41].…”
Section: Ephb3mentioning
confidence: 99%
“…Moreover, several studies have confirmed a role for PP2A in the control of cell migration. 123,124 Finally, proteomic analyses have identified SET in complex with a host of cellular proteins including the Rac/Cdc42 GEF βPIX and the Rac/Cdc42 effector PAK1, 125 actin and dynamin-2 119 and a β1-integrin-filamin complex. 126 A recent study by Switzer et al 127 showed that a SET-binding peptide (COG112) does not only block the Rac1-SET interaction, but also reduces EGF-induced Rac1 activation and serum-induced cell migration and invasion.…”
mentioning
confidence: 99%
“…As a result, its dysregulation may contribute to tumorigenesis. In fact, RACK1 has been demonstrated to be involved in various types of malignant tumors including hepatocellular carcinoma, lung cancer, colon cancer, prostate cancer, cervical carcinoma, oral squamous cell carcinoma and neuroblastoma (13)(14)(15)(16)(17)(18)(19). However, whether RACK1 plays a role in malignant glioma as well as the mechanism involved remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%